A 1536-Well 3D Viability Assay to Assess the Cytotoxic Effect of Drugs on Spheroids. (June 2017) - Madoux, Franck; Tanner, Allison; Vessels, Michelle; Willetts, Lynsey; Hou, Shurong; Scampavia, Louis; Spicer, Timothy P.
Evaluation of drug cytotoxicity traditionally relies on use of cell monolayers, which are easily miniaturized to the 1536-well plate format. Three-dimensional (3D) cell culture models have recently gained popularity thanks to their ability to better mimic the complexity of in vivo systems. Despite growing interest in these more physiologically relevant and highly predictive cell-based models for compound profiling and drug discovery, 3D assays are currently performed in a medium- to low-throughput format, either in 96-well or 384-well plates. Here, we describe the design and implementation of a novel high-throughput screening (HTS)–compatible 1536-well plate assay that enables the parallel formation, size monitoring and viability assessment of 3D spheroids in a highly consistent manner. Custom-made plates featuring an ultra-low-attachment surface and round-bottom wells were evaluated for their compatibility with HTS requirements through a luminescence-based cytotoxicity pilot screen of ~3300 drugs from approved drug and National Cancer Institute (NCI) collections. As anticipated, results from this screen were significantly different from a parallel screen performed on cell monolayers. With the ability to achieve an average Z′ factor greater than 0.5, this automation-friendly assay can be implemented to either profile lead compounds in a more economical plate format or to interrogate large compound libraries by ultra-HTS (uHTS).